Tracing motivational emergence in a classroom language learning project. (June 2015) - Sampson, Richard J.
Abstract: In order to generalise about the EFL motivation of Japanese classroom learners, much research has utilised large-scale, quantitative methods. However, recent theorising of language learner motivation is reflective of a more interactive and complex understanding of the situated nature of motivation. This paper describes a qualitative study into the contextualised motivation of one class of first-grade students at a Japanese college of technology. As part of a one-year longitudinal action research study, rich qualitative data in the form of student and teacher journals revealed a clear parallel between the complex systems concept of "emergence" and the development of motivation across the class group in a final, six-week project. In order to understand the development of this particular whole-class motivational outcome, a process similar to retrodictive qualitative modelling (Dörnyei, 2014) was used to work backwards by (i) describing the key features of the emergent outcome; (ii) identifying common forms of interaction in the system during the six-week project, and (iii) using complex systems theory to understand some of the fundamental conditions of the emergence. The paper lends support for the usefulness of complex systems theory to foster more adequate representations of the dynamic, co-forming development of motivation in classroom settings.